Use of extracts of sunflower-seed oil (Helianthus annus L.) for the treatment of cutaneous injuries in equine metatarsus: a case report Uso do óleo de semente de girassol (Helianthus annus) no tratamento de lesões cutâneas no metatarso de um equino: relato de caso - C.S. Coelho; J.A.N. Gama; L.A.T. Oliveira Júnior; B.S.F. Silva; V.R.C. Souza; D.C. Endringer; D Lenz (Universidade Estadual Paulista, 2012)
This study describes an eighteen-year-old filly after an injury in the region of the dorsal left metatarsus, admitted to veterinary assistance. In addition to the normal treatment, which was characterized by cleaning and topical application of povidone-iodine, sunflower-seed oil was applied locally in order to improve and fasten wound healing. Macroscopic and clinical improvements of the wound healing were observed. The preliminary chemical and physical analyses have shown the stearic acid as the main component. The results suggest that the sunflower-seed oil enable a faster wound healing in horses. O presente relato se refere a uma potra de 18 meses de idade que foi encaminhada a atendimento veterinário após sofrer grave lesão na região dorsal do metatarso esquerdo. Além do tratamento convencional, caracterizado pela limpeza e aplicação tópica de iodo-povidine, foi aplicado no local óleo de semente de girassol na tentativa de melhorar e acelerar a cicatrização da ferida. Foi observada a melhora clínica e macroscópica da lesão. Análises preliminares químicas e físicas demonstraram o ácido esteárico como principal componente do óleo usado. Os resultados sugerem que o óleo de semente de girassol é capaz de acelerar e melhorar a qualidade de cicatrização em feridas de equinos.